Institutional Relational Maintenance Barriers and Perceptions of Relationship Quality Among Women With Incarcerated Partners - Durante, Katherine A. (Crime & delinquency, 2024)
High rates of incarceration in the United States has prompted researchers to study the impacts of imprisonment on romantic relationships and minor children. We examine the relationship between several prison facility barriers to relational maintenance and perceptions of relationship quality from the perspective of women whose male romantic, coparenting partners are incarcerated. Using data from the Multi-site Family Study on Incarceration, Parenting and Partnering (MFS-IP) and binomial logistic regression, we find that the high costs of phone calls and difficulty of in-person visitation negatively impact how women perceive romantic relationship quality. These findings suggest that alleviating barriers to contact can help strengthen couples? relationships.